Preparation and mechanical properties of strong and tough poly (vinyl alcohol)-polypeptide double-network hydrogels. (February 2018) - Ge, Chenglong; Ling, Ying; Yan, Shunjie; Luan, Shifang; Zhang, Haowen; Tang, Haoyu
Graphical abstract: The stiffness and toughness of the poly(vinyl alcohol) (PVA) hydrogels can be significantly improved (e.g., 6.3 times the Young's modulus and 5.8 times the work of extension) by incorporation of small amount of ionic liquid (IL)-based polypeptides. The strong and tough double-network hydrogel was constructed by PVA crystallites and ionic bonds of IL-based polypeptide as the double physical cross-linkers. Highlights: We prepared poly(vinyl alcohol)-polypeptide double-network hydrogels. We examined the effect of polymer structure parameter on mechanical properties. Mechanical properties were significantly improved by incorporation of polypeptides. Abstract: Poly(vinyl alcohol) (PVA)-polypeptide double-network hydrogels with various ionic liquid (IL)-based polypeptides were prepared by a freezing/thawing method. Tensile tests revealed that the stiffness and toughness of the PVA hydrogels were significantly improved (e.g., 6.3 times the Young's modulus and 5.8 times the work of extension) by incorporation of IL-based polypeptides. An optimized mechanical property was achieved by incorporation of α-helical imidazolium-based polypeptides at x = 0.03. Rheological tests revealed a thermally induced transition at 51.4–58.1 °C for the double network PVA/PPLG-ImBF4 - x -67 ( x = 0.01, 0.02, 0.03) hydrogels due to the rupture of the electrostatic interactions. Field emission scanning electron microscopy (FESEM) and wide-angle X-ray diffraction (WAXD) results suggested that the strong and tough double-network hydrogel was constructed by PVA crystallites and ionic bonds of IL-based polypeptide as the double physical cross-linkers.